2013
DOI: 10.1371/journal.pone.0069618
|View full text |Cite
|
Sign up to set email alerts
|

A Lover and a Fighter: The Genome Sequence of an Entomopathogenic Nematode Heterorhabditis bacteriophora

Abstract: Heterorhabditis bacteriophora are entomopathogenic nematodes that have evolved a mutualism with Photorhabdus luminescens bacteria to function as highly virulent insect pathogens. The nematode provides a safe harbor for intestinal symbionts in soil and delivers the symbiotic bacteria into the insect blood. The symbiont provides virulence and toxins, metabolites essential for nematode reproduction, and antibiotic preservation of the insect cadaver. Approximately half of the 21,250 putative protein coding genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 122 publications
2
110
0
Order By: Relevance
“…These differences in virulence reflect differences in both the rates at which fly larvae become infected with EPNs and the rates at which infected fly larvae succumb to the infection. All five of the Drosophila species tested have sequenced genomes (60), and six of the seven nematode species tested have sequenced or nearly sequenced genomes (61,62). A comparison of Drosophila genomes revealed that many immune-related genes evolve more rapidly than other genes and identified numerous species-specific differences in immune-related genes, including copy number differences in AMP genes (63).…”
Section: Resultsmentioning
confidence: 99%
“…These differences in virulence reflect differences in both the rates at which fly larvae become infected with EPNs and the rates at which infected fly larvae succumb to the infection. All five of the Drosophila species tested have sequenced genomes (60), and six of the seven nematode species tested have sequenced or nearly sequenced genomes (61,62). A comparison of Drosophila genomes revealed that many immune-related genes evolve more rapidly than other genes and identified numerous species-specific differences in immune-related genes, including copy number differences in AMP genes (63).…”
Section: Resultsmentioning
confidence: 99%
“…e.g. [2][3][4][5] Included in this list are those of two root-knot nematodes (RKN), Meloidogyne hapla 2 and Meloidogyne incognita. 3 Meloidogyne is a large genus of plant parasites that are distributed worldwide and cause substantial loss to agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since these nematode-bacterium complexes are pathogenic toward a wide range of insects, an additional goal in studying EPNs is improving their employability in insect pest control (Stock 2005). In particular, investigators are focusing on identifying EPNs traits associated with insect host range and successful parasitism to help improve their field efficacy, and on identifying EPN symbiont products with insecticidal properties, efforts facilitated by sequencing of both bacterial and nematode genomes (Duchaud et al 2003;Ciche 2007;Wilkinson et al 2009;Chaston et al 2011;Dillman, Mortazavi and Sternberg 2012;Bai et al 2013).…”
Section: The Perfect Middlementioning
confidence: 99%